2012
DOI: 10.1098/rsbl.2012.0079
|View full text |Cite
|
Sign up to set email alerts
|

RNAi of the circadian clock geneperioddisrupts the circadian rhythm but not the circatidal rhythm in the mangrove cricket

Abstract: The clock mechanism for circatidal rhythm has long been controversial, and its molecular basis is completely unknown. The mangrove cricket, Apteronemobius asahinai , shows two rhythms simultaneously in its locomotor activity: a circatidal rhythm producing active and inactive phases as well as a circadian rhythm modifying the activity intensity of circatidal active phases. The role of the clock gene period ( per ), one of the key components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…Unfortunately, it was not possible to test its effect on activity modulation because the act of injection compromised the rhythm. A recent study of the mangrove cricket has also sought to examine whether knockdown of period by dsRNAi disrupts tidal and circadian rhythms of locomotion [35]. These insects show locomotor cycles, which have a tidal periodicity and an amplitude modulation of the tidal behavioral episodes, much like Eurydice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it was not possible to test its effect on activity modulation because the act of injection compromised the rhythm. A recent study of the mangrove cricket has also sought to examine whether knockdown of period by dsRNAi disrupts tidal and circadian rhythms of locomotion [35]. These insects show locomotor cycles, which have a tidal periodicity and an amplitude modulation of the tidal behavioral episodes, much like Eurydice.…”
Section: Discussionmentioning
confidence: 99%
“…These insects show locomotor cycles, which have a tidal periodicity and an amplitude modulation of the tidal behavioral episodes, much like Eurydice. The authors have suggested that knockdown of period gene expression disrupts the modulation of locomotor rhythms but not the tidal periodicity, and they concluded that the circadian clock does not underlie the tidal clock [35]. However, scrutiny of the data presented suggests that period knockdown impacts negatively on both the putative circadian and tidal components.…”
Section: Discussionmentioning
confidence: 99%
“…To match the rise and fall of the tide, many inhabitants exhibit circatidal biological rhythms, which allow organisms to anticipate and respond accordingly to predictable daily changes in tidal height (Tessmar-Raible et al, 2011;Wilcockson and Zhang, 2008). There is increasing evidence that these rhythms are driven by an endogenous time-keeping circatidal clock because they persist even when tidal cues are removed (Takekata et al, 2012;Zhang et al, 2013). The most thoroughly characterized circatidal rhythms are behavioral and many intertidal inhabitants will exhibit periods of foraging activity that are coordinated with the tidal cycle (reviewed in Palmer, 1973Palmer, , 1975 and with changes in tidal height (Stillman and Barnwell, 2004).…”
Section: Biological Rhythms In An Intertidal Habitatmentioning
confidence: 99%
“…The circatidal rhythm generates active and inactive phases, and the circadian rhythm modifies the circatidal rhythm by inhibiting activity during the subjective day (Satoh et al, 2008). Although the results of period knocking down suggest the circatidal rhythm is considered to be generated by a molecular mechanism different from that of the circadian rhythm, the neural components of the 2 rhythms are still unknown (Takekata et al, 2012). The circadian modulation, however, entrains to light-dark cycles.…”
mentioning
confidence: 99%